Liquid chromatographic methods for determination of the new antiepileptic drugs stiripentol, retigabine, rufinamide and perampanel: A comprehensive and critical review - Meirinho, Sara (2021)
The new antiepileptic drugs perampanel, retigabine, rufinamide and stiripentol have been recently approved for different epilepsy types. Being them an innovation in the antiepileptics armamentarium, a lot of investigations regarding their pharmacological properties are yet to be performed. Besides, considering their broad anticonvulsant activities, an extension of their therapeutic indications may be worthy of investigation, especially regarding other seizure types as well as other central nervous system disorders. Although different liquid chromatographic (LC) methods coupled with ultraviolet, fluorescence, mass or tandem-mass spectrometry detection have already been developed for the determination of perampanel, retigabine, rufinamide and stiripentol, new and more cost-effective methods are yet required. Therefore, this review summarizes the main analytical aspects regarding the liquid chromatographic methods developed for the analysis of perampanel, retigabine (and its main active metabolite), rufinamide and stiripentol in biological samples and pharmaceutical dosage forms. Furthermore, the physicochemical and stability properties of the target compounds will also be addressed. Thus, this review gathers, for the first time, important background information on LC methods that have been developed and applied for the determination of perampanel, retigabine, rufinamide and stiripentol, which should be considered as a starting point if new (bio)analytical techniques are aimed to be implemented for these drugs.